Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

Long working hours increase the risk of insufficient dietary diversity: Findings among online ride-hailing drivers - Binshuo Hu; Cheng Chang; Xin Song; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Hong Yu; Li Guan; Dongsheng Niu; Jue Li; Rui Guan; Tenglong Yan (Appetite, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

A novel electrostatic-assisted airflow pollination end-effector for kiwifruit flowers with optimized charging and spraying parameters - Yusong Ding; Leilei He; Juncai Huang; Xin Wei; Yufei Shi; Hin Lim; Spyros Fountas; Shaojin Wang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Grafting-engineered biomass-based quasi-solid composite electrolyte with suppressed filler aggregation and enhanced interfacial compatibility for high-performance solid-state lithium metal batteries - Peilin Ding; Xian Pan; Xin Zhou; Tao Li; Rui Xiao; Shiliang Wu (Chemical Engineering Journal, 2026)

Light-confining resonant metamaterial integrated with silicon-doped quantum dots for liquid-phase biomolecular detection - Rui Zhang; Jie Huang; Lanju Liang; Zhuyu Ding; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun (Chemical Engineering Journal, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Modulating the metal–support interaction of Pt/CeO2 catalysts for enhanced chemodynamic therapy for lung cancer thearanostics - Meijuan Ding; Tao Jia; Rui Xin; Guanghua Cui; Xiaoke Sun; Jialu Guo; Lili Feng; Yu Yang (Chemical Engineering Journal, 2025)

Assessing the nicotinic acetylcholine receptor-mediated enantioselective neurotoxicity of a neonicotinoid-like pollutant, chiral sulfoxaflor: Insight from the two asymmetric centers - Zhi-Cong He; Tao Zhang; Xin-Fang Lu; Rui Li; Wei Peng; Qiong Mei; Qi-Zhao Wang; Fei Ding (Journal of Hazardous Materials, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

A novel dual-network CO2-responsive particle gel for mitigating CO2 channeling and leakage in hydrocarbon recovery and carbon storage - Yang Zhao; Xin Wen; Zhenhua Rui; Yanxu Ding (Chemical Engineering Journal, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Novel insights into the relationship between the functional groups and photoactivity of biochar-derived dissolved organic matter - Xin Zuo; Zhuozhi Ouyang; Jinmo Liao; Rui Ding; Weiwei Zhang; Chi Zhang; Xuetao Guo; Lingyan Zhu (Water Research, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Photocatalytic degradation of benzotriazole through synergy of electron donor–acceptor units and Au clusters in covalent organic frameworks - Hui Wang; Yuhan Xiong; Yi He; Lingru Kong; Lan Ding; Rui Wu; Xin-Lei Gao; Jie Ding; Nanqi Ren (Chemical Engineering Journal, 2024)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Spatiotemporal analysis of bike mobility chain: A new perspective on mobility pattern discovery in urban bike-sharing system - Rui Xin; Jian Yang; Bo Ai; Linfang Ding; Tingting Li; Ruoxin Zhu (Journal of Transport Geography, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Distinguishing the contributions of hot holes from interband and intraband transitions to the photoenhanced electrocatalytic oxidation reaction of ethanol - Chen Chi; Miao Ni; Xin-Lei Ding; Dong-Rui Yang; Jian Li; Xing-Hua Xia (Science Bulletin, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Recovery of nickel, phosphorus and nitrogen from electroless nickel-plating wastewater using bipolar membrane electrodialysis - Yaoxing Liu; Xiaoyu Wu; Xiaoyun Wu; Liping Dai; Jianguo Ding; Xin Ye; Riyao Chen; Rui Ding; Jianxi Liu; Yanchao Jin; Bart Van der Bruggen (Journal of Cleaner Production, 2023)

High-resolution Simulation of an Extreme Heavy Rainfall Event in Shanghai Using the Weather Research and Forecasting Model: Sensitivity to Planetary Boundary Layer Parameterization - Rui Wang; Yiting Zhu; Fengxue Qiao; Xin-Zhong Liang; Han Zhang; Yang Ding (Advances in Atmospheric Sciences, 2021)

Research on differences of spillover effects between international crude oil price and stock markets in China and America - Zhenhua Liu; Zhihua Ding; Rui Li; Xin Jiang; JyS. Wu; Tao Lv (Natural Hazards, 2017)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

MicroRNA-1228* inhibit apoptosis in A549 cells exposed to fine particulate matter - Xiaobo Li; Zhen Ding; Chengcheng Zhang; Xin Zhang; Qingtao Meng; Shenshen Wu; Shizhi Wang; Lihong Yin; Yuepu Pu; Rui Chen (Environmental Science and Pollution Research, 2016)

Preparation of malathion MIP-SPE and its application in environmental analysis - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Lei Shi; Ming Xing; Ping Guo; Yuan Ding; Hong Yang (Environmental Monitoring and Assessment, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Overexpression of PeHSF mediates leaf ROS homeostasis in transgenic tobacco lines grown under salt stress conditions - Zedan Shen; Mingquan Ding; Jian Sun; Shurong Deng; Rui Zhao; Meijuan Wang; Xujun Ma; Feifei Wang; Huilong Zhang; Zeyong Qian; Yue Hu; Rui Yu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)